Sticky Platelet Syndrome: An Unrecognized Cause of Acute Thrombosis and Graft Loss - Fabio Solis-Jimenez; Hector Hinojosa-Heredia; Luis García-Covarrubias; Virgilia Soto-Abraham; Rafael Valdez-Ortiz (Case Reports in Nephrology)
Introduction. Sticky platelet syndrome (SPS) is a prothrombotic disease that is not well recognized and difficult to diagnose. Case Report. We present a case of a 49-year-old diabetic woman on ambulatory peritoneal dialysis therapy who underwent a kidney transplant from living-related donor. The donor was her sister with whom she shared one haplotype and absence of donor specific antibodies. The posttransplant evolution was torpid, developing progressive deterioration, which made us suspect a failure in the graft. Doppler ultrasound reported renal vein thrombosis and hypoperfusion of the renal artery. Without clinical improvement, she required a reintervention that ended in graftectomy, in which the histopathological report showed negative C4d with medullary and cortical infarction. Hematological studies were negative for antibodies against phospholipids, with correct levels of proteins C and S and antithrombin. Platelet aggregometry studies were carried out, which were compatible with SPS. Conclusions. Recognition of SPS in pretransplant studies is difficult if there is no history of previous thrombotic events. However, we must consider this entity in cases of acute thrombosis and loss of the graft of uncertain origin.